Management of relational databases of herbaceous plants using neural networks and fazzy logic - Anhar Mohammed; Suhair Abd Dawood (College of Education for Pure Sciences, 2008)
The research aim is to design a system that help the user which want agriculture some of types of plantago with adequate way without losing in effort, Time & money through designing of general computer database about this plantago & understanding its behavior and sensitivity to light and temperature by connecting database with fuzzy logic, so number from fuzzy logical bases are shaping to know the growth ratio for the seeds of a number from the kinds of the planted plantago, the membership functions connecting within the every one of its variables. We connect Backpropagation Neural Network with Fuzzy Logic to appoint the Type (classifying) of Plantago which growths . The database is designed by using(Microsoft Access)and is programmed by using Visual Basic Ver. 6 and works With Windows Me.